2011
DOI: 10.1002/etc.748
|View full text |Cite|
|
Sign up to set email alerts
|

Myriophyllum aquaticum versus Lemna minor: Sensitivity and recovery potential after exposure to atrazine

Abstract: The relative sensitivity and recovery potential of two aquatic macrophyte species, Lemna minor and Myriophyllum aquaticum, exposed to atrazine (concentration ranges 80-1,280 µg/L and 40-640 µg/L, respectively) were evaluated using slightly adapted standard protocol for Lemna spp.: relative growth rates (RGR) and yield of both plants were measured in 3-d-long intervals during the exposure and recovery phase. Myriophyllum aquaticum was also exposed to atrazine-spiked sediment (0.1-3.7 µg/g) in a water-free syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Atrazine acts by inhibiting photosystem-II of photosynthesis through competitive and noncovalent binding of the QB site of the D1 protein (Jensen et al, 1977;Jursinic and Stemler, 1983;Shimabukuro et al, 1970). Consequently, inhibition is reversible immediately upon removal of atrazine, and recovery of both terrestrial and aquatic plant communities under a variety of conditions has been demonstrated (Jensen et al, 1977;Shimabukuro et al, 1970;Klaine et al, 1996;Brain et al, 2012aBrain et al, , 2012bBrockway et al, 1984;Hughes et al, 1988;Jones et al, 1986;Juttner et al, 1995;Teodorović et al, 2012;Mohammad et al, 2008Mohammad et al, , 2010Stay et al, 1989;Vallotton et al, 2008). In a variety of algal species, both biochemically and physiologically, recovery of photosynthesis and growth rate occur immediately, reaching control levels within hours following exposure to atrazine at concentrations much higher than typically encountered in situ (250-1000 μg/L) (Vallotton et al, 2008;Brain et al, 2012aBrain et al, , 2012bHughes et al, 1988).…”
Section: Inertia Explained By Variable Group and By Individual Variablesmentioning
confidence: 93%
“…Atrazine acts by inhibiting photosystem-II of photosynthesis through competitive and noncovalent binding of the QB site of the D1 protein (Jensen et al, 1977;Jursinic and Stemler, 1983;Shimabukuro et al, 1970). Consequently, inhibition is reversible immediately upon removal of atrazine, and recovery of both terrestrial and aquatic plant communities under a variety of conditions has been demonstrated (Jensen et al, 1977;Shimabukuro et al, 1970;Klaine et al, 1996;Brain et al, 2012aBrain et al, , 2012bBrockway et al, 1984;Hughes et al, 1988;Jones et al, 1986;Juttner et al, 1995;Teodorović et al, 2012;Mohammad et al, 2008Mohammad et al, , 2010Stay et al, 1989;Vallotton et al, 2008). In a variety of algal species, both biochemically and physiologically, recovery of photosynthesis and growth rate occur immediately, reaching control levels within hours following exposure to atrazine at concentrations much higher than typically encountered in situ (250-1000 μg/L) (Vallotton et al, 2008;Brain et al, 2012aBrain et al, , 2012bHughes et al, 1988).…”
Section: Inertia Explained By Variable Group and By Individual Variablesmentioning
confidence: 93%
“…This is an indication of the functionality and the efficiency of the photosystem and a powerful tool in addition to the growth parameters to detect stress in plants. In a recent comparative study [18], the toxicity of atrazine was in the same range for M. aquaticum without the adaptation phase and Lemna minor (EC50 M. aquaticum 93.51 μg/L respective EC50 L. minor 121.85 μg/L). 2,4-D represents synthetic auxine herbicides, which are in the focus of the discussion regarding the necessity of additional macrophyte biotests [8,9,11].…”
mentioning
confidence: 99%
“…The study contributes to the characterization of Cu toxicity to M. aquaticum ; however, it does not enable the assessment of risks of Cu‐contaminated natural sediments. Until now, the M. aquaticum test was mainly used for the assessment of potential effects of pesticides in sediment ; our results show that it can also be an interesting tool for the assessment of Cu‐contaminated sediments.…”
Section: Discussionmentioning
confidence: 81%